Breastfeeding practices and infant feeding pattern of a tribal population region of eastern India - Sarkar, Deblina (J Family Med Prim Care, 2020)
BACKGROUND: Regular vigilance over infant feeding practices in the community is necessary for assessment of optimal growth and development and the intervention if needed. OBJECTIVE: To illustrate infant feeding practices, and socio-demographically correlated time like when weaning starts, the challenges met by mothers, and the types of complementary feeding adopted. METHODS: A structured pretested and predesigned questionnaire was used to collect information regarding sociodemographic, detail information regarding initiation and duration of breastfeeding, age of complementary feeding and type of food given during complementary feeding, minimum dietary diversity and minimum meal frequency, and also advice given during child feeding session. RESULTS: The study revealed that it was a predominantly Hindu tribal community where majority of infant were female and belong to joint families. Most of the mother had completed high secondary school and were housewives and belong to upper lower social class. Majority of women had more than two children, and rate of delivery at government institution was more than private institution and home delivery. Exclusive breastfeeding was practiced among 78% of infants, 46% had started breastfeeding within 1 h of birth. In total, 48% of infants were given prelacteal feed, and colostrum feeding was practiced among 62% of infants. Complementary feeding was given by 82% of infants and minimum dietary diversity, and minimum meal frequency was found among 77 and 85%, respectively. CONCLUSION: This community-based study carried out among tribal population of Kalyani showed that exclusive breastfeeding and other domains like complementary feeding and minimum dietary diversity are almost satisfactory.